Leaf senescence and the profile of expanded leaf area in maize (Zea mays L.) - Valentinuz, Oscar Rodolfo (University of Guelph, 2022)
Tesis para obtener el grado de Doctor of Philosophy, de la University of Guelph, en 2002.